Infection induces a positive acute phase apolipoprotein E response from a negative acute phase gene: role of hepatic LDL receptors*s⃞ - Li Li (Journal of Lipid Research, 2008)
Apolipoprotein E (apoE) plays important roles in lipid homeostasis, anti-inflammation, and host defense. Since tissue apoE mRNA levels have been reported to decrease during inflammatory responses, we were surprised to find that plasma apoE levels were significantly elevated during septic infections in both humans and mice. This apparent paradox was also observed during lipopolysaccharide-induced acute inflammation in mice: plasma levels of apoE increased up to 4-fold despite sharply decreased apoE gene expression in the liver, macrophages, and extrahepatic tissues. We hypothesized that apoE levels were augmented by decreased plasma clearance. Our analysis revealed that apoE associated principally with HDL in mice and that apoE was cleared from the circulation principally via LDL receptors. The acute inflammatory response decreased LDL receptor expression in the liver and significantly reduced the rate of apoE clearance. In contrast, the same inflammatory stimuli increased LDL receptor expression in macrophages. Our results define a novel acute phase mechanism that increases circulating apoE levels as apoE production decreases. Diminished hepatic LDL receptor expression may thus cooperate with elevated LDL receptor expression in macrophages to facilitate the forward transport of apoE and its associated lipids to these key defense cells.